Studi Prospektif Pemakaian Stent Bioaktif Pada Intervensi Koroner Perkutan Primer - Yoga Yuniadi (The Indonesian Heart Association, 2011)
Background. Limited data are available on efficacy and safety of bioactive stent implantation in acute STEMI patient. This study aims to evaluate efficacy titanium nitrit-oxide stent implantation during primary percutaneous coronary intervention.Methods and Results. Thirty eight patients (age of 55.9 ± 8.35 years) presenting with less than 12 hours onsetacute STEMI enrolled in this study. After titanium nitrit oxide bioactive stent implantation then 12 months clinical follow up was performed. Infarct location were anterior (58%) and Killip class I (82%) in majority of cases. Average door to balloon time is 85.7 ± 33.88 minutes. Cilprit lesions have characteristics of simple lesion as it comprised of almost 90% of denovo and 60.5% were type A lesion. Proportion of history of myocardial infarction is higher in patients experienced of MACE but other characteristics were similar as compare to non-MACE group. MACE-free survival is 83.6% during 12 months follow up.Conclusion. In our population, implantation of bioactive stent during primary PCI of STEMI patient is safe and effective. Twelve months MACE-free survival is similar to other study using similar stent or drug eluting stent.